PEMBANGUNGAN INFRASTRUKTUR SISTEM JARINGAN UNTUK MENDUKUNG ERA TEKNOLOGI INFORMASI DAN KOMUNIKASI DESA TERTINGGAL - Jarot Sugiharto (UPPM Politeknik TEDC Bandung, 2015)
Development of information and communication technologies (ICT) is rapidly and the potential for widespread utilization provide opportunities for access, management, and utilization of information quickly and accurately, which in turn will bring the community is currently experiencing a change or transformation towards a more advanced and more efficient.Telecommunication network infrastructure is the components which important and vital part to speed up the process of implementing the information and communication technology in an area. Rural district is one of the districts in the provinces East of Indonesia should be ready to meet the century's information and telecommunication systems, utilizing and managing future to manage community resources and the natural resources that exist in all area. Keyword : ICT, rural network telecommunication